2018
DOI: 10.3389/fnagi.2018.00055
|View full text |Cite
|
Sign up to set email alerts
|

Altered Brain Functional Hubs and Connectivity in Type 2 Diabetes Mellitus Patients: A Resting-State fMRI Study

Abstract: Type 2 diabetes mellitus (T2DM) affects a vast population and is closely associated with cognitive impairment. However, the mechanisms of cognitive impairment in T2DM patients have not been unraveled. Research on the basic units (nodes or hubs and edges) of the brain functional network on the basis of neuroimaging may advance our understanding of the network change pattern in T2DM patients. This study investigated the change patterns of brain functional hubs using degree centrality (DC) analysis and the connec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
27
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(30 citation statements)
references
References 54 publications
3
27
0
Order By: Relevance
“…DC quantifies local degree, which measures the centrality of every voxel in the human brain connectome ( 22 , 24 ). The increased DC may imply the transition from an economic connection to the costly connection; that is, brain regions with high energy-consumption such as brain hubs can be reconfigured to meet different and variable cognitive needs through negotiations between connection costs and the topological characteristics of the networks ( 39 , 40 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…DC quantifies local degree, which measures the centrality of every voxel in the human brain connectome ( 22 , 24 ). The increased DC may imply the transition from an economic connection to the costly connection; that is, brain regions with high energy-consumption such as brain hubs can be reconfigured to meet different and variable cognitive needs through negotiations between connection costs and the topological characteristics of the networks ( 39 , 40 ).…”
Section: Discussionmentioning
confidence: 99%
“…DC has been widely used to quantify node features of networks, and increased DC regions are defined as functional hubs (22). Previous researches using DC analysis showed altered brain functional hubs and connectivity in T2DM subjects (5,23,24). However, subjects enrolled in these studies had clinical cognitive impairment or lacked cognitive assessment.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have also confirmed that DC has a high sensitivity, specificity, and test-retest reliability, (Zuo and Xing 2014) and it has been increasingly used in many disorders associated with cognitive impairment, such as obstructive sleep apnea, diabetes, Parkinson's, and Alzheimer's disease. (Li et al 2016;Liu et al 2018;Wang et al 2018;Guo et al 2016) Therefore, the voxel-wise DC can help us investigate the intrinsic function hubs that may be associated with cognitive impairment in COPD.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies had investigated regional CBF changes in the right-handed subjects with cerebrovascular diseases in the postcentral gyrus and found that the left somatosensory cortex has a dominant role in sensorimotor integration for complex finger movements (25), whereas visuospatial is lateralized to the right hemisphere (26). Previous fMRI studies also confirmed the decreased connectivity among the right precentral gyrus and bilateral lateral occipital cortices in diabetes (27). Since all the subjects in this study were right-handed, we cannot rule out the influence of cerebral dominance in the observed CBF asymmetries.…”
Section: Discussionmentioning
confidence: 87%